Media use and preference related to coronary heart disease of the coloured population of the Cape Peninsula the crisic study - M. Steyn; K. Steyn (AOSIS, 1989)
As a part of a comprehensive coronary risk factor study among the coloured population of the Cape Peninsula (the CRISIC study), the media use and preference of the population were examined with a view to suggesting appropriate media for conveying health messages. A stratified sample (N = 976) was randomly drawn from the coloured population in the age group 15 to 64 years in the Cape Peninsula. Data were collected by means of a pre-tested questionnaire. Analysis of the data showed that information on the prevention of heart disease was obtained in greater measure from the mass media than from interpersonal communication. As far as media preference is concerned, television was considered the most effective medium for conveying information to the community, followed by instruction given to school children. Greater use of health educators to convey health messages, as well as a multi-media approach, is suggested for a successful intervention programme.